(untitled) (European Journal of Interdisciplinary Research and Development, 2024)
Research helps forecast corporate financial success by using performance assessment indicators, detecting and mitigating aberrations in light of evaluation outcomes, and illustrating the significance of performance evaluation and its influence on better performance. The company that produces ready-made clothing and is listed on the Iraqi Stock Exchange served as the research sample. The study’s time frame was set between 2018 and 2020. An analytical and deductive approach was taken, and the hypothesis that the use of financial performance evaluation indicators aids in "predicting and improving performance in the ready-made clothing production company" was relied upon in order to accomplish the goal. According to the research, the total amount of current costs reached its greatest levels in 2020 (17379359739) dinars. The year in question saw a notable fluctuation in trading ratios between high and low points during the research period, despite the fact that net sales for that year totaled (17364229241) dinars and the expenses to sales ratio of 100%, the highest percentage ever achieved during the research period. The value of current assets (6679746025) dinars and the value of current liabilities (8490473655) dinars in 2019 were (82%), and the value of current liabilities (5864917028) and the value of current assets (6679755162) dinars in 2020 were (11%), the lowest percentages. In other words, the firm can pay its current liabilities with its current assets, demonstrating its capacity to maintain a balance between the two and proving that it can make its payments on time and within reasonable limits. It suggested that financial policy makers should focus more on examining the performance indicators between liquidity and market value of financial companies and reveal profitability and market value indicators in financial statements, since they show how strong financial companies and their stocks are relative to one another.